Avaliação de desempenho térmico de edificação pública em Cuiabá, MT: estudo de caso - Campos, Nadine Lessa Figueiredo (2012)
Considering the global scenario of scarce natural resources, creating solutions for moreresponsible energy consumption becomes essential. The architectural design appropriate to theclimate minimizes the energy consumption during use of the building. Aiming at reducing theenergy consumption of buildings were developed performance standards and energy efficiency invarious countries. In this context, this study aims at evaluating the thermal performance of apublic building in the city of Cuiabá, MT. To this end, measurements were made on the spotassessment of thermal comfort by the method of Fanger, evaluation of the envelope by RTQ-C.The building had a good thermal performance in their evaluations, staying in the comfort zoneduring all business hours. It is hoped that with this work, Regulation and its application can bebroadcast in the city of Cuiabá, demonstrating its effectiveness and contributing to improvedenergy efficiency of local buildings, especially for public buildings.